.8(3x-9)+14=4(.4x+7)

Simple and best practice solution for .8(3x-9)+14=4(.4x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .8(3x-9)+14=4(.4x+7) equation:


Simplifying
0.8(3x + -9) + 14 = 4(0.4x + 7)

Reorder the terms:
0.8(-9 + 3x) + 14 = 4(0.4x + 7)
(-9 * 0.8 + 3x * 0.8) + 14 = 4(0.4x + 7)
(-7.2 + 2.4x) + 14 = 4(0.4x + 7)

Reorder the terms:
-7.2 + 14 + 2.4x = 4(0.4x + 7)

Combine like terms: -7.2 + 14 = 6.8
6.8 + 2.4x = 4(0.4x + 7)

Reorder the terms:
6.8 + 2.4x = 4(7 + 0.4x)
6.8 + 2.4x = (7 * 4 + 0.4x * 4)
6.8 + 2.4x = (28 + 1.6x)

Solving
6.8 + 2.4x = 28 + 1.6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1.6x' to each side of the equation.
6.8 + 2.4x + -1.6x = 28 + 1.6x + -1.6x

Combine like terms: 2.4x + -1.6x = 0.8x
6.8 + 0.8x = 28 + 1.6x + -1.6x

Combine like terms: 1.6x + -1.6x = 0.0
6.8 + 0.8x = 28 + 0.0
6.8 + 0.8x = 28

Add '-6.8' to each side of the equation.
6.8 + -6.8 + 0.8x = 28 + -6.8

Combine like terms: 6.8 + -6.8 = 0.0
0.0 + 0.8x = 28 + -6.8
0.8x = 28 + -6.8

Combine like terms: 28 + -6.8 = 21.2
0.8x = 21.2

Divide each side by '0.8'.
x = 26.5

Simplifying
x = 26.5

See similar equations:

| 4(2d-d)-6d-8=2d | | (4a-5)(5a+3)=0 | | n-4+1=5 | | 3v+2(1-4)=7 | | 3(b+4)=36+b | | 44x^2-11=0 | | 30n=-27n-36 | | 44x^2+11=0 | | y=1.6(25)+1 | | 19k-1+k= | | 19p=-19 | | 2z^2+iz=0 | | y=1.6(20)+1 | | y=1.6(15)+1 | | 25b+11=-6b | | 19k-1k= | | y=1.6(10)+1 | | 4(-5n+2)=6(1-3n) | | 3g-10=8 | | -8(1m-5)=25-5m | | 4a+7=11+a | | (N-2)180=178 | | a(n-7)+9=bn | | y=1.6(-0)+1 | | 12-5h=3h-4 | | 11x^2=x^2+7 | | 180-x(3+x)=108 | | 12=-3(x-1)-6 | | y=1.6(-1)+1 | | 4c+9-c=-15 | | c=3m+10 | | Y=1.6(-2)+1 |

Equations solver categories